Comparison of productivity from three stingless bees: Tetragonula sapiens, T. clypearis and T. biroi managed under same feed sources for meliponiculture - ERWAN ERWAN; HABIBURROHMAN HABIBURROHMAN; I KETUT GEDE WIRYAWAN; MUHAMMAD MUHSININ; BAMBANG SUPENO; AGUSSALIM AGUSSALIM (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Erwan, Habiburrohman, Wiryawan IKG, Muhsinin M, Supeno B, Agussalim. 2023. Comparison of productivity from three stingless bees: Tetragonula sapiens, T. clypearis and T. biroi managed under same feed sources for meliponiculture. Biodiversitas 24: 2988-2994. The productivity of stingless bee species is affected by the workers' population, especially the foragers' number, queen bee productivity, and the availability of plants as the nectar and pollen sources. The recent study aims to evaluate the productivity of three stingless bee species, Tetragonula sapiens (Cockerell, 1911), Tetragonula clypearis (Friese, 1908), and Tetragonula biroi (Friese, 1898), managed under the same feed sources for beekeeping in stingless bee (meliponiculture). Total of fifteen colonies and every five colonies per species of T. sapiens, T. clypearis, and T. biroi, respectively. The results showed that the different species of stingless bees highly affected the exit activities in the morning and afternoon and brood cell number (p<0.01). Furthermore, significant impacts on the honey pot number, production of honey and propolis (p<0.05) but not on the pollen pot number and the production of pot-pollen. Thus, productivity was characterized by honey pot number, brood cell number, and production of honey and propolis from the stingless bee of T. biroi was higher than T. sapiens and T. clypearis. However, the productivity of T. sapiens and T. clypearis was similar.